Sorafenib plus topotecan versus placebo plus topotecan for platinum-resistant ovarian cancer (TRIAS): a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Issue 9 (September 2018) - Chekerov, Radoslav; Hilpert, Felix; Mahner, Sven; El-Balat, Ahmed; Harter, Philipp; De Gregorio, Nikolaus; Fridrich, Claudius; Markmann, Susanne; Potenberg, Jochem; Lorenz, Ralf; Oskay-Oezcelik, Guelten; Schmidt, Marcus; et al.
Summary: Background: Antiangiogenic therapy has known activity in ovarian cancer. The investigator-initiated randomised phase 2 TRIAS trial assessed the multi-kinase inhibitor sorafenib combined with topotecan and continued as maintenance therapy for platinum-resistant or platinum-refractory ovarian cancer. Methods: We did a multicentre, double-blind, placebo-controlled, randomised, phase 2 trial at 20 sites in Germany. Patients (≥18 years) with platinum-resistant ovarian cancer previously treated with two or fewer chemotherapy lines for recurrent disease were stratified (first vs later relapse) in block sizes of four and randomly assigned (1:1) using a web-generated response system to topotecan (1·25 mg/m 2 on days 1–5) plus either oral sorafenib 400 mg or placebo twice daily on days 6–15, repeated every 21 days for six cycles, followed by daily maintenance sorafenib or placebo for up to 1 year in patients without progression. Investigators and patients were masked to allocation of sorafenib or placebo; topotecan treatment was open label. The primary endpoint was investigator-assessed progression-free survival, analysed in all patients who received at least one dose of study drug. This completed trial is registered withClinicalTrials.gov, numberNCT01047891 . Findings: Between Jan 18, 2010, and Sept 19, 2013, 185 patients were enrolled, 174 of whom were randomly assigned: 85 to sorafenib and 89 to placebo. Two patients in the sorafenib group had serious adverse events before treatment and were excluded from analyses. 83 patients in the sorafenib group and 89 in the placebo group started treatment. Progression-free survival was significantly improved with sorafenib versus placebo (hazard ratio 0·60, 95% CI 0·43–0·83; p=0·0018). Median progression-free survival was 6·7 months (95% CI 5·8–7·6) with sorafenib versus 4·4 months (3·7–5·0) with placebo. The most common grade 3–4 adverse events were leucopenia (57 [69%] of 83 patients in the sorafenib group vs 47 [53%] of 89 in the placebo group), neutropenia (46 [55%] vs 48 [54%]), and thrombocytopenia (23 [28%] vs 20 [22%]). Serious adverse events occurred in 49 (59%) of 83 sorafenib-treated patients and 45 (51%) of 89 placebo-treated patients. Of these, events were fatal in four patients (5%) in the sorafenib group (dyspnoea and poor general condition, septic shock, ascites and dyspnoea, and sigma perforation) and seven (8%) in the placebo group (pulmonary embolism in two patients, disease progression in two patients, and one case each of sepsis with fever, pleural effusion, and tumour cachexia). Sorafenib was associated with increased incidences of grade 3 hand-foot skin reaction (three [13%] vs 0 patients) and grade 2 alopecia (24 [29%] vs 12 [13%]). Interpretation: Sorafenib, when given orally in combination with topotecan and continued as maintenance therapy, showed a statistically and clinically significant improvement in progression-free survival in women with platinum-resistant ovarian cancer. These encouraging results support the crucial role of antiangiogenesis as the treatment backbone in combination with chemotherapy, making this approach attractive for further assessment with other targeted strategies. Funding: Bayer, Amgen, and GlaxoSmithKline.